2012
DOI: 10.1007/s10856-012-4618-2
|View full text |Cite
|
Sign up to set email alerts
|

Fiber reinforcement of a biomimetic bone cement

Abstract: In this study we investigated the influence of electrospun polymer fibers on the properties of a α-tricalcium phosphate/gelatin biomimetic cement. To this aim, we added different amounts of poly(L-lactic acid) and poly(lactide-co-glycolide) fibers to the cement composition. Fibers enrichment provoked a significant reduction of both initial and final setting times. Moreover electrospun polymer fibers slowed down the conversion of α-tricalcium phosphate into calcium deficient hydroxyapatite. As a result, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The addition of electrospun poly(lactic acid) and poly(lactic-co-glycolic acid) fibers maintained the mechanical properties of CPC-gelatin cements for longer periods of time. 25 However, the mechanical properties of the incorporated CPC were still not sufficient to ensure CPC application in load-bearing bones. This is largely due to the poor structural interface that exists between the hydrophobic polymer and the hydrophilic mineral.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of electrospun poly(lactic acid) and poly(lactic-co-glycolic acid) fibers maintained the mechanical properties of CPC-gelatin cements for longer periods of time. 25 However, the mechanical properties of the incorporated CPC were still not sufficient to ensure CPC application in load-bearing bones. This is largely due to the poor structural interface that exists between the hydrophobic polymer and the hydrophilic mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of an α-TCP-based cement with electrospun fibers of poly(L-lactic acid) and poly(lactide-co-glycolide) was found to slow down the conversion of α-TCP to calcium-deficient HA, with a consequent reduction of crystal dimensions and crystallinity of the apatitic phase, which yielded fiber-reinforced cements able to maintain their mechanical properties in the long term (Fig. 4) (106). Incorporation of electrospun poly(D,L-lactide- co -glycolide) into a CPC consisting of TTCP, DCPA and chitosan lactate increased the flexural strength twofold, and toughness by an order of magnitude, compared with the control cement (107).…”
Section: Bone Cementsmentioning
confidence: 99%
“…44 Panzavolta et al found that electrospun PLA or poly(lactic-co-glycolic acid) (PLGA) bre-reinforced CPC-gelatine cements were able to maintain the mechanical strength and the elastic modulus for longer periods of time than the CPC-gelatine cement. 45…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…87 In vivo, bone healing and regeneration are driven by the action of a number of growth factors, and a popular strategy for enhancing osteoprogenitor and osteoblast functionality is the incorporation of growth, adhesion, and transcription factors into a synthetic material. 45 Chow suggested that the incorporation of an osteoinductive factor, such as bone morphogenetic proteins (BMPs), which are well-recognised bone-inductive proteins, could be one of the most effective ways to improve the efficacy of CPC materials for repairing defects with insufficient available bone surfaces. 87 In animal studies, superior osteoinductivity has been shown when BMPs are loaded onto CPC-based implants.…”
Section: Osteoinductivitymentioning
confidence: 99%